Genome-wide diversity assessment for genetic resource management of Eucalyptus dunnii, E. grandis, E. nitens and E. urophylla - Myburg, Alexander Andrew (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2021.